Clinical trial: a controlled trial of baclofen add‐on therapy in PPI‐refractory gastro‐oesophageal reflux symptoms. Issue 2 (3rd June 2022) - Pauwels, Ans; Raymenants, Karlien; Geeraerts, Annelies; Boecxstaens, Veerle; Masuy, Imke; Broers, Charlotte; Vanuytsel, Tim; Tack, Jan
Summary: Background: Proton pump inhibitors (PPI) have no effect on non‐acid reflux events which can continue to provoke gastro‐oesophageal reflux disease (GERD) symptoms. Baclofen, a γ‐aminobutyric acid agonist, can decrease non‐acid reflux but its symptomatic benefit in refractory GERD symptoms is understudied. Aims: To assess the efficacy of baclofen 10 mg t.i.d. vs placebo as add‐on therapy in PPI‐refractory GERD symptoms, in a randomised, double‐blind, placebo‐controlled study. Methods: Patients with persisting typical GERD symptoms on b.i.d. PPI therapy were randomised to 4 weeks of baclofen 10 mg or placebo t.i.d. Before and after treatment, patients underwent 24 h impedance‐pH monitoring on‐PPI. Throughout the study, patients filled out ReQuest diaries. Data were analysed using mixed models. Results: About 60 patients were included (age 47.5 years [range 19–73], 41f/19 m), 31 patients were randomised to baclofen. One patient withdrew consent and five in the baclofen group stopped treatment due to side effects. There was a trend towards a better response for general wellbeing in the baclofen‐treated group compared to placebo ( p  = 0.06). When subdividing patients according to symptom association probability (SAP), only the SAP+ ( n  = 25) group improved significantly with baclofen ( p corr  = 0.02), and worsened with placebo ( p corr  = 0.008). The total number of reflux events decreased over time ( p  = 0.01), mainly due to the baclofen condition ( p corr  = 0.1). The number of reflux events with a high proximal extent dropped significantly after baclofen ( p corr  = 0.009), but not placebo. Conclusion: Baclofen decreases several reflux parameters in PPI refractory GERD symptoms, but pH‐impedance monitoring is necessary before treatment as only SAP+ patients experience clinical benefit after 4 weeks. Abstract : Baclofen add‐on for refractory GERD symptoms.